Synthesis and properties of polyaniline, poly(o-anisidine), and poly[aniline-co-(o-anisidine)] using potassium iodate oxidizing agent. (April 2017) - Neetika, Manglik; Rajni, Jain; Singh, Pramod K; Bhattacharya, B; Singh, Vijay; Tomar, SK
Polyaniline (PANI), poly( o -anisidine), and poly[aniline-co-( o -anisidine)] were synthesized by chemical oxidative polymerization with potassium iodate as an oxidizing agent in a hydrochloric acid (HCl) medium. The self-doped, doped, and undoped forms of these polymers were characterized by infrared spectroscopy, ultraviolet–visible spectroscopy, and the conductivity method. The observed decrease in the conductivity of the copolymer and poly( o -anisidine) with respect to PANI was attributed to the incorporation of methoxy moieties into the PANI chain. The homopolymer attained conductivity in the range of 3.75 × 10 −3 to 7.40 S cm −1 after doping with HCl. The conductivity of the undoped form of poly[aniline-co-( o -anisidine)] and poly( o -anisidine) was observed to be lower than 10 −5 S cm −1 . The conductivity of the polymer sample decreased in the following order: PANI → poly[aniline-co-( o -anisidine)] → poly( o -anisidine). The undoped form of poly[aniline-co-( o -anisidine)] had good solubility in common organic solvents.